The mediating effect of academic experience on the relationship between personal resilience and satisfaction of students registered in student assistance (Research, Society and Development, 2020)
Bearing in mind that each student has distinct resilience characteristics that help him to face the difficulties that interfere with his academic satisfaction, the general objective of this work was to verify the impact of personal resilience and academic experience on the satisfaction of students registered in student assistance for a Federal University. As for the methods and procedures, a quantitative approach was used, in which an online questionnaire was applied to students registered in the student assistance of this university for data collection, with a return of 493 complete answers. Data analysis was performed using the Structural Equation Modeling technique, using the Smart-PLS software. The results showed that personal resilience positively impacts the student's academic experience and that this in turn positively impacts student satisfaction with the University. On the other hand, it was found that personal resilience does not directly impact satisfaction, only indirectly, through academic experience. Thus, the academic experience is presented as a mediating factor in this relationship. Furthermore, the proposed model was able to explain 65.20% of the students' satisfaction with the University.